THE ROLE OF PANCASILA AND CITIZENSHIP EDUCATION IN STRENGTHENING NATIONAL INSIGHT - Maria Lidia Elsiani Meo; Fredik Lambertus Kollo; Anjulin Yonathan Kamlasi; Angelita Revalina Tallo Ati; Nobertus Deni Cuan (FISIP Universitas Malikussaleh, 2026)
Pancasila and Civic Education (PPKn) has a strategic rolein building national character while strengthening national awareness inthe midst of the challenges of globalisation, information flows, and increasinglycomplex social changes. This study is based on the phenomenon of weakening nationalismand civic attitudes among the younger generation, which is characterised by a decline inlove for the country, low awareness of Pancasila values, andrampant intolerance. The purpose of this study is to analyse the role ofPPKn in strengthening students' national awareness. The method usedis qualitative analysis with a descriptive approach, namely examining datafrom literature, policy documents, and relevant previous research results. The analysis was conducted by examining the relationship between the objectives of PPKn, its application in learning, and its impact on the understanding of national values. The results of the study show that PPKn plays an important role as a means of internalising Pancasila values, developing democratic attitudes, andinstilling awareness of the rights and obligations of citizens. PPKn can be aneffective instrument in strengthening national insight if it is implemented in acontextual, participatory manner and integrated with the real lives of students. Therefore, optimising Civic Education learning is a strategic stepin maintaining national unity and strengthening national identity.